Clinical applications of extracellular vesicles: recent advances and emerging trends - Zou, Yitan; Zhou, Yaping; Li, Guangyao; Dong, Yuchao; Hu, Shi (Frontiers in Bioengineering and Biotechnology, 2025)
Extracellular vesicles (EVs) have emerged as pivotal mediators of intercellular communication and promising theranostic agents in medicine. These naturally-derived nanoparticles possess unique advantages including stable physicochemical properties, low immunogenicity, and inherent biocompatibility. In recent years, increasing attention has been directed toward clinical investigations. Driven by these clinical studies, several EV-based diagnostic and therapeutic products have emerged. In this review, we aimed to highlight and discuss the completed and emerging clinical investigations of EV-based strategies, critically elucidate persistent technical and translational hurdles impeding clinical implementation, and propose strategic directions to accelerate realization of the transformative potential inherent in EV-mediated precision medicine.